1997
DOI: 10.1172/jci119231
|View full text |Cite
|
Sign up to set email alerts
|

Absence of P-selectin delays fatty streak formation in mice.

Abstract: P-selectin is expressed on activated endothelium and platelets where it can bind monocytes, neutrophils, stimulated T cells, and platelets. Because recruitment of these cells is critical for atherosclerotic lesion development, we examined whether P-selectin might play a role in atherosclerosis. We intercrossed P-selectin-deficient mice with mice lacking the low density lipoprotein receptor (LDLR) because these mice readily develop atherosclerotic lesions on diets rich in saturated fat and cholesterol. The athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
1
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(171 citation statements)
references
References 47 publications
(41 reference statements)
2
164
1
4
Order By: Relevance
“…As described in the introduction, using LDLR-deficient mice fed the atherogenic diet, we found that the absence of P-selectin partially reduces fatty streak formation but does not affect the more advanced stages of atherosclerosis. 8 The present study is the first to demonstrate that P-selectin is also important for lesion growth at the fibrous plaque stage.…”
Section: Dong Et Al P-selectin In Advanced Atherosclerosis 2293mentioning
confidence: 50%
See 2 more Smart Citations
“…As described in the introduction, using LDLR-deficient mice fed the atherogenic diet, we found that the absence of P-selectin partially reduces fatty streak formation but does not affect the more advanced stages of atherosclerosis. 8 The present study is the first to demonstrate that P-selectin is also important for lesion growth at the fibrous plaque stage.…”
Section: Dong Et Al P-selectin In Advanced Atherosclerosis 2293mentioning
confidence: 50%
“…The sections containing aortic sinus were prepared as described, 8 with modifications. The heart and attached aorta were fixed in 4% paraformaldehyde for 30 minutes before being embedded in OCT compound.…”
Section: Quantification Of Aortic Sinus Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 It should be noted that ICAM-1 expression is only part of the mechanism implicated in the homing of leukocytes to sites of vascular lesions; other adhesion molecules, for instance, P-selectin, have been implicated in gene-deleted mice. 43 Furthermore, knocking out MCP-1 or its receptor in LDL Ϫ/Ϫ or ApoE Ϫ/Ϫ mice, respectively, will also significantly decrease lesion formation. 44,45 In conclusion, adhesion and transmigration mediated by several interacting molecular mechanisms appear to be essential for monocyte traffic in atherosclerosis, and this study provides further evidence of the importance of these phenomena in the pathogenesis of the disease.…”
Section: Bourdillon Et Al Vascular Lesions In Apoe/icam-1-deficient Micementioning
confidence: 99%
“…In the more realistic apoE knockout model of atherosclerosis, in which mice have cholesterol levels between 500 and 2,000 mg/dl, depending on the diet offered, animals lacking P-selectin or ICAM-1 show significantly smaller aortic lesions (13,14). In a milder model of atherosclerosis, the LDL receptor knockout mouse, absence of P-selectin showed only a modest benefit in male mice and no benefit in female mice (15).…”
mentioning
confidence: 99%